Pengaruh E-Servicescape, Persepsi Manfaat, Kelengkapan Informasi Dan Kepercayaan Terhadap Keputusan Berbelanja Online Di Shopee: Studi Kasus Pada Ibu Rumah Tangga Di Kelurahan Tambangan Kota Tebing Tinggi - Muhammad Hilalul Hamdhi; Fitrianingsih Fitrianingsih; Imelda Mardayanti; Muhammad Wahyu Hamijaya (Digital Business Progress, 2023)
This study aims to determine how the influence of E-Servicescape, Perception of Benefits, Completeness of Information and Trust on Online Shopping Decisions at Shopee. The population used in this study were housewives in the Mining Village, Cliff Tinggi City, who used the Shopee application for an unknown amount. Because the population is not known in determining the number of samples used Cochran method. Regression analysis method used is multiple linear regression and to test the hypothesis used t test and f test. The research data were analyzed or processed using the SPSS version 25 program. From the results of this study, it can be concluded that e-servicescape has an effect on purchasing decision variables. Perceived benefits affect the purchasing decision variables. Completeness of information affects the purchasing decision variables. Trust has no effect on purchasing decisions.